Accuracy of burn size estimation in patients transferred to adult Burn Units in Sydney, Australia: An audit of 698 patients. Issue 1 (February 2015) - Harish, Varun; Raymond, Andrew P.; Issler, Andrea C.; Lajevardi, Sepehr S.; Chang, Ling-Yun; Maitz, Peter K.M.; Kennedy, Peter
Abstract Background The purpose of this study was to compare burn size estimation between referring centres and Burn Units in adult patients transferred to Burn Units in Sydney, Australia. Methods A review of all adults transferred to Burn Units in Sydney, Australia between January 2009 and August 2013 was performed. The TBSA estimated by the referring institution was compared with the TBSA measured at the Burns Unit. Results There were 698 adults transferred to a Burns Unit. Equivalent TBSA estimation between the referring hospital and Burns Unit occurred in 30% of patients. Overestimation occurred at a ratio exceeding 3:1 with respect to underestimation, with the difference between the referring institutions and Burns Unit estimation being statistically significant (P < 0.001). Significant overestimation occurs in the early transfer of burn-injured patients as well as in patients transferred more than 48 h after the burn (P < 0.005). Underestimation occurs with less frequency but rises with increasing time after the burn (P < 0.005) and with increasing TBSA. Throughout the temporal spectrum of transferred patients, severe burns (≥20% TBSA) were found to have more satisfactory burn size estimations compared with less severe injuries (<20% TBSA; P < 0.005). Conclusions There are significant inaccuracies in burn size assessment by referring centres. The systemic tendency for overestimation occurs throughout the entire TBSA spectrum, and persists with increasing time after the burn. Underestimation occurs less frequently but rises with increasing time after the burn and with increasing TBSA. Severe burns (≥20% TBSA) are more accurately estimated by the referring hospital. The inaccuracies in burn size assessment have the potential to result in suboptimal treatment and inappropriate referral to specialised Burn Units.